Effect of Introgression of Pup1 Locus on Rice Seedling under Phosphorus Deficiency - Nurul Hidayatun; Joko Prasetiyono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
The lack of soil-phosphorus (P) element will result in plant growth retardation. Plants could survive in P deficiency stress by increasing the ability of P uptake or by increasing the efficiency in the P utilization. The aims of this study were to understand genetic composition of rice genotypes possessing Pup1 locus and to know root and leaf growth responses at different P availability condition. The three rice genotypes (IR74, IR74-Pup1, and Kasalath) were analyzed for their genetic composition using SNP markers. The phenotypic experiment was arranged using a Completely Randomized Design with four replications and performed hydroponically in nutrient solution with different availability of P. The result showed that IR74-Pup1 had 84.4% similarities to its parent (IR74) with 13.6% of donor segments, where the Pup1 locus located. The influence of Pup1 locusintrogression on total length, surface area, diameter, and volume of the root varied at each growth stage. IR74 and IR74-Pup1 had root and leaf growth restriction on low P, but Pup1 locus introgression showed better growth performance, both in normal P and in low P conditions. The introgression of Pup1 locus increases plant ability to reduce the impact of growth inhibitioncaused by P deficiency.